2018
DOI: 10.1016/j.foreco.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between large high-severity fires and salvage logging on a short return interval reduce the regrowth of fire-prone serotinous forests

Abstract: New fire disturbance regimes under accelerating global environmental change can have unprecedented consequences for ecosystem resilience, lessening ecosystem natural regeneration. In the Mediterranean Basin, fire-dependent obligate seeder forests that are prone to increasingly frequent stand-replacing fires and then salvaged logged repeatedly can be vulnerable to additional disturbances for decades. In this study, we investigated, for the first time, the cumulative and interactive effects of two large high-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 73 publications
(136 reference statements)
1
35
0
Order By: Relevance
“…Similarly, Knapp and Ritchie (2016) attributed reduced shrub cover and richness to mechanical impacts of salvage logging, but noted that, of the multiple functional groups and life-history categories assessed, only shrubs were significantly impacted. Taboada et al (2018) reported that, after a single fire, salvage logging did not impact forest recovery, but with two fires, reduced seedling establishment was amplified by salvage logging. Soil nutrient levels and ecologically important exchangeable cations were reduced as well (Bowd et al 2019).…”
Section: Fire and Salvage Loggingmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Knapp and Ritchie (2016) attributed reduced shrub cover and richness to mechanical impacts of salvage logging, but noted that, of the multiple functional groups and life-history categories assessed, only shrubs were significantly impacted. Taboada et al (2018) reported that, after a single fire, salvage logging did not impact forest recovery, but with two fires, reduced seedling establishment was amplified by salvage logging. Soil nutrient levels and ecologically important exchangeable cations were reduced as well (Bowd et al 2019).…”
Section: Fire and Salvage Loggingmentioning
confidence: 99%
“…For instance, reduced postfire regeneration was attributed to seed source reduction by a preceding fire (Taboada et al 2018), bark beetle outbreak (Harvey et al 2013), and clearcut logging operation (Ton and Krawchuk 2016). For instance, reduced postfire regeneration was attributed to seed source reduction by a preceding fire (Taboada et al 2018), bark beetle outbreak (Harvey et al 2013), and clearcut logging operation (Ton and Krawchuk 2016).…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations